Cover Picture: Spectroscopic and Computational Characterizations of Alkaline‐Earth‐ and Heavy‐Metal‐Exchanged Natrolites (ChemPlusChem 8/2014). Issue 8 (18th July 2014) - Liu, Dan; Chen, Xin; Ma, Yanming; Liu, Zhenxian; Vogt, Thomas; Lee, Yongjae
<x xml:space="preserve">Abstract</x> The cover picture shows the natrolite framework of a small‐pore zeolite made up of alternating SiO4 and AlO4 tetrahedral 4‐rings and helical 8‐rings, which can contain, via cooperative rotation of the 4‐rings and subsequent modification of the 8‐ring opening, monovalent alkali metals Li+, Na+, K+, Rb+ and Cs+, divalent alkaline‐earth ions Ca2+, Sr2+ and Ba2+ as well as heavy metals like Cd2+, Pb2+ and Ag+ as charge‐balancing extra‐framework cations (EFC). In their Full Paper on on page 1096 ff., Y. Lee and co‐workers report that the vibrational frequencies of both 4‐ and helical 8‐ring units scale with the size of the EFC and that the frequency of the HOH bending and OH stretching modes of water contained within the pores are dependent on the orientations of the water molecules along the natrolite channel. Deviations from these correlations in mixed EFC natrolites could hint at new structures owing to size‐driven phase separations.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>